Effects of training on performance in competitive swimming - Mujika, I.; Chatard, J. C.; Busso, T.; Geyssant, A.; Barale, F.; Lacoste, L. (Canadian Journal of Applied Physiology, 1995)
The relationships between the mean intensity of a training season, training volume and frequency, and the variations in performance were studied in a group of 18 elite swimmers. Additionally, differences between the swimmers who improved their personal record of the previous year during the follow-up training season (GIR, n = 8) and those who did not (GNI, n = 10) were investigated. The improvement in performance during the follow-up season was significantly correlated with the mean intensity of the training season (r = 0.69, p < 0.01), but not with training volume or frequency. The performance improvement during the follow-up season was negatively related to the initial performance level (r = 0.90, p < 0.01). The decline in performance during detraining from the previous year was less for the GIR than for the GNI (6.21 +/- 2.30% vs. 9.79 +/- 2.18%, p < 0.01). The present findings suggest that training intensity is the key factor in performance improvement in a group of elite swimmers. Factors such as previous detraining and initial performance level could jeopardize success in spite of a good adaptation to training.